2023
DOI: 10.3390/biomedicines11082287
|View full text |Cite
|
Sign up to set email alerts
|

‘Spikeopathy’: COVID-19 Spike Protein Is Pathogenic, from Both Virus and Vaccine mRNA

Peter I. Parry,
Astrid Lefringhausen,
Conny Turni
et al.

Abstract: The COVID-19 pandemic caused much illness, many deaths, and profound disruption to society. The production of ‘safe and effective’ vaccines was a key public health target. Sadly, unprecedented high rates of adverse events have overshadowed the benefits. This two-part narrative review presents evidence for the widespread harms of novel product COVID-19 mRNA and adenovectorDNA vaccines and is novel in attempting to provide a thorough overview of harms arising from the new technology in vaccines that relied on hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 211 publications
1
37
0
Order By: Relevance
“…A study of more than 50,000 employees at a medical institution in the United States observed the incidence of the Omicron variant epidemic based on the number of vaccine doses received (0, 1, 2, 3, and 4 or more doses) over a period of 26 weeks and showed that the number of vaccines received was positively correlated with the cumulative incidence rate of COVID-19 [ 46 ]. Susceptibility to COVID-19 infection after multiple vaccinations may be enhanced by antibody-dependent enhancement [ 47 ], immune imprinting [ 39 , 48 ], and immunosuppression [ 25 - 27 ]. This can result in a risk of exposure to viral S-protein in addition to vaccine S-protein for the multiple-vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…A study of more than 50,000 employees at a medical institution in the United States observed the incidence of the Omicron variant epidemic based on the number of vaccine doses received (0, 1, 2, 3, and 4 or more doses) over a period of 26 weeks and showed that the number of vaccines received was positively correlated with the cumulative incidence rate of COVID-19 [ 46 ]. Susceptibility to COVID-19 infection after multiple vaccinations may be enhanced by antibody-dependent enhancement [ 47 ], immune imprinting [ 39 , 48 ], and immunosuppression [ 25 - 27 ]. This can result in a risk of exposure to viral S-protein in addition to vaccine S-protein for the multiple-vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the development of numerous vaccines for the prevention of COVID-19 and approval of several drugs for its treatment, there is still a great need for effective and inexpensive therapy of this disease. Additionally, it should be mentioned that initial expectations regarding efficacy and safety of SARS-CoV-2 vaccines were, probably, exaggerated (see [13] for review). In this overall context, green tea catechins, are considered as promising because of their antiviral effects against SARS-CoV-2, while EGCG was reported as most effective (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The SAEs reported with the mRNA-LNP platform are very diverse. The SAEs are likely caused by the combination of the mRNA-LNP vaccine components (103) and potentially by direct toxicity and biological action of the spike protein itself (104)(105)(106)(107)(108). Here, we will focus on SAEs likely mediated by the immune system.…”
Section: Mrna-lnp-associated Adverse Eventsboth Inflammatory and Inhi...mentioning
confidence: 99%